2003
DOI: 10.1128/cdli.10.6.1019-1024.2003
|View full text |Cite
|
Sign up to set email alerts
|

Multilaboratory Evaluation of a Viability Assay for Measurement of Opsonophagocytic Antibodies Specific to the Capsular Polysaccharides of Streptococcus pneumoniae

Abstract: Opsonophagocytosis is a correlate of protection that measures the functional activity of vaccine-induced antibodies. A standardized opsonophagocytosis assay (OPA) should be used as part of the evaluation of current and future pneumococcal (Pnc) polysaccharide (Ps)-based vaccines. We enrolled five laboratories to evaluate a previously standardized viability OPA. Each laboratory was provided with a detailed OPA protocol, seven target Pnc strains (serotypes 4, 6B, 9V, 14, 18C, 19F, and 23F), two quality control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 26 publications
2
53
0
Order By: Relevance
“…In contrast, several experienced European laboratories in various countries reported difficulties in achieving reproducible differentiation of HL-60 cells into granulocytes with DMF. Although some European laboratories were successful in using HL-60 (72), these diverse international experiences became a concern in adopting the HL-60 derived granulocytes as the effector cells for pneumococcal OPAs.…”
Section: Hl-60 a Problem Cell Line?mentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, several experienced European laboratories in various countries reported difficulties in achieving reproducible differentiation of HL-60 cells into granulocytes with DMF. Although some European laboratories were successful in using HL-60 (72), these diverse international experiences became a concern in adopting the HL-60 derived granulocytes as the effector cells for pneumococcal OPAs.…”
Section: Hl-60 a Problem Cell Line?mentioning
confidence: 99%
“…Maintenance of HL-60 is possible in RPMI 1640 supplemented with 2 mM L-Glutamine and 10 to 20% heat-inactivated FBS from various sources (HyClone, Logan, Utah; JRH Biosciences, Lenexa, Kans.) (29,72). Under these conditions, HL-60 cultures can be maintained by diluting the cells with a fresh medium to a density of 10 5 viable cells/ml when the cell density reaches 10 6 cells/ml.…”
Section: Hl-60 Cell Line Maintenance and Passagementioning
confidence: 99%
See 2 more Smart Citations
“…In previous work, we characterized human opsonophagocytic antibodies recognizing nontypeable Haemophilus influenzae by using an assay modified from one developed for the measurement of antibodies against Streptococcus pneumoniae (51,52). In that earlier work, we demonstrated that antibodies directed against the HMW1/ HMW2-like proteins were major contributors to the opsonophagocytic activity mediated by naturally acquired human antibodies (65).…”
Section: Discussionmentioning
confidence: 99%